The Genetic Diversity and Geographic Differentiation of the Wild Soybean in Northeast China Based on Nuclear Microsatellite Variation. (6th June 2018) - Zhao, Hongkun; Wang, Yumin; Xing, Fu; Liu, Xiaodong; Yuan, Cuiping; Qi, Guangxun; Guo, Jixun; Dong, Yingshan
Abstract : In this study, the genetic diversity and population structure of 205 wild soybean core collections in Northeast China from nine latitude populations and nine longitude populations were evaluated using SSR markers. A total of 973 alleles were detected by 43 SSR loci, and the average number of alleles per locus was 22.628. The mean Shannon information index (I ) and the mean expected heterozygosity were 2.528 and 0.879, respectively. At the population level, the regions of 42°N and 124°E had the highest genetic diversity among all latitudes and longitudes. The greater the difference in latitude was, the greater the genetic distance was, whereas a similar trend was not found in longitude populations. Three main clusters (1N, <41°N-42°N; 2N, 43°N-44°N; and 3N, 45°N–>49°N) were assigned to populations. AMOVA analysis showed that the genetic differentiation among latitude and longitude populations was 0.088 and 0.058, respectively, and the majority of genetic variation occurred within populations. The Mantel test revealed that genetic distance was significantly correlated with geographical distance (r = 0.207, p < 0.05 ). Furthermore, spatial autocorrelation analysis showed that there was a spatial structure (ω = 119.58, p < 0.01 ) and the correlation coefficient (r ) decreased as distance increased within a radius of 250 km.